DIRECTIVE SPEECH ACTS OF THE COUNT DRACULA IN DRACULA NOVEL - Lestari, Siska (Jurnal Ilmiah Spectral, 2020)
This study focused on describing types and functions of the directive speech act on Dracula's novel. The study used a descriptive qualitative method in which Dracula’s utterances were collected. It has found eighteen of Dracula’s utterances. Out of eighteen utterances, ten utterances were directive speech acts which have a function to stating and commanding, three utterances belong to requesting speech acts, two utterances were questioning, while three utterances belong to prohibiting, asking, and advisories speech act. The data analyzed has proved that there are four functions of directive speech acts based on Levinsons’ principle and three functions based on Allan. It is concluded that the directive speech act is the way how the speaker influences the addressee to do something.